PENGARUH METODE BRAINSTORMING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN MATERI SISTEM PENCERNAAN MANUSIA - Mona Desti Ersa; Elvira Destiansari; Syarifah Syarifah; Tiara Dwi Anjani (Bioilmi: Jurnal Pendidikan, 2023)
The conventional learning method are educators results in the learning process becoming boring and hindering the students' way of thinking in comprehending a material. This study aims to obtain data and the influence of the use of brainstorming learning methods on the critical thinking skills of class VIII students on the material of the human digestive system. This research was conducted at SMP Negeri 40 Palembang. The research design used was nonequivalent control group with quasi-experimental design. The research sample used was class VIII.3 as an experimental class totaling 32 students and class VIII.4 as a control class totaling 32 students. Data collection was taken using interview techniques, tests of critical thinking questions, and documentation. The results of the data analysis show that the brainstorming method has an influence on students' critical thinking skills. This can be seen from the t-test results that show that the value of tcount> ttable (3,447>2,042) or the significance value is less than 0.05 (0.001<0.05) then H0 is rejected and H1 is accepted. The average results of the experimental class data analysis reached 73.59; while the control class reached 63,69 meaning that the critical thinking ability of the experimental class students was higher than the control class's critical thinking ability. The method of brainstorming influences the critical thinking skills.